2019
DOI: 10.1111/jocn.15135
|View full text |Cite
|
Sign up to set email alerts
|

Wound care practices across two acute care settings: A comparative study

Abstract: Aims and objectives Describe and compare current surgical wound care practices across two hospitals in two health services districts, Australia. Background Surgical site infections (SSI) are a complication of surgery and occur in up to 9.5% of surgical procedures, yet they are preventable. Despite the existence of clinical guidelines for SSI prevention, there remains high variation in wound care practice. Design Prospective comparative design using structured observations and chart audit. Methods A specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
1
22
1
2
Order By: Relevance
“…In addition, we found that most HCWs have more than six years' experience in carrying out the wound dressing procedure since they are typically older than 30 years of age. Contrastingly, this finding does not support other studies which state that the greater the age of HCWs, the more likely they are to be involved in wound dressing (Gillespie et al, 2020). Thus, we posit that wound dressing responsibilities have no correlation with HCW's experience.…”
Section: Recommendationcontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that most HCWs have more than six years' experience in carrying out the wound dressing procedure since they are typically older than 30 years of age. Contrastingly, this finding does not support other studies which state that the greater the age of HCWs, the more likely they are to be involved in wound dressing (Gillespie et al, 2020). Thus, we posit that wound dressing responsibilities have no correlation with HCW's experience.…”
Section: Recommendationcontrasting
confidence: 99%
“…It is also assumed that wound healing has been under the aegis of basic nursing practice (Sen, 2019). In today standard, nurses will often spend an estimated 25-50% of their time dealing with various types of wounds, which typically range from acute wounds, such as simple lacerations, to more chronic wounds, such as bedsores or diabetic leg ulcers (Gillespie et al, 2020). Although nurses play a crucial role handling wound related procedure, it is not uncommon in today practice that other non-nurse Health Care Worker (HCW) getting involved in managing the wound care.…”
Section: Introductionmentioning
confidence: 99%
“…Los profesionales y las organizaciones de salud pública deben aplicar estrategias de prevención de sepsis integral, para minimizar las complicaciones y mejorar el pronóstico de los pacientes (26)(27)(28)(29)(30).…”
Section: Discussionunclassified
“…Thus, there may be a potential bias due to the self-selecting nature of the sampling. Yet nurses provide the bulk of wound care (Gillespie et al, 2019). Third, we recognise that individuals were self-selecting, and inevitably may promote a personal or institutional perspective.…”
Section: Limitationsmentioning
confidence: 98%